A dominant role for the immunoproteasome in CD8+ T cell responses to murine cytomegalovirus. - Hutchinson, S; Sims, S; O'Hara, G; Silk, J; Gileadi, U; Cerundolo, V; Klenerman, P (Public Library of Science, 2011)
Murine cytomegalovirus (MCMV) is an important animal model of human cytomegalovirus (HCMV), a (Beta)-Herpesvirus that infects the majority of the world's population and causes disease in neonates and immunocompromised adults. CD8(+) T cells are a major part of the immune response to MCMV and HCMV. Processing of peptides for presentation to CD8(+) T cells may be critically dependent on the immunoproteasome, expression of which is affected by MCMV. However, the overall importance of the immunoproteasome in the generation of immunodominant peptides from MCMV is not known. We therefore examined the role of the immunoproteasome in stimulation of CD8(+) T cell responses to MCMV - both conventional memory responses and those undergoing long-term expansion or "inflation". We infected LMP7(-/-) and C57BL/6 mice with MCMV or with newly-generated recombinant vaccinia viruses (rVVs) encoding the immunodominant MCMV protein M45 in either full-length or epitope-only minigene form. We analysed CD8(+) T cell responses using intracellular cytokine stain (ICS) and MHC Class I tetramer staining for a panel of MCMV-derived epitopes. We showed a critical role for immunoproteasome in MCMV affecting all epitopes studied. Interestingly we found that memory "inflating" epitopes demonstrate reduced immunoproteasome dependence compared to non-inflating epitopes. M45-specific responses induced by rVVs remain immunoproteasome-dependent. These results help to define a critical restriction point for CD8(+) T cell epitopes in natural cytomegalovirus (CMV) infection and potentially in vaccine strategies against this and other viruses.